Application of Traditional Chinese Medicines in Diabetes Mellitus: From Pathogenesis to Clinical Practice - Yuan, Shaojing; Zhao, Yue; Xing, Wei; Han, Tao; Yang, Junzheng (Current Pharmaceutical Biotechnology, 2026)
Diabetes mellitus (DM) is a group of metabolic disorders characterised by insufficient insulin secretion and reduced insulin sensitivity in target tissues, leading to a range of metabolic abnormalities. DM has a profound global impact and exerts detrimental effects on patients’ health. Traditional Chinese Medicines (TCMs), characterised by dialectical treatment principles and a holistic therapeutic philosophy, have been shown to play an important role in the management and alleviation of DM. In this review, we provide a concise overview of recent applications of TCMs in DM, summarise the underlying mechanisms, and discuss both the limitations of current practices and future prospects in this field. Numerous non-clinical and clinical studies have demonstrated the significant therapeutic advantages of TCMs in improving and alleviating DM. However, limitations persist, including variability among TCM formulations, the scarcity of high-quality randomised clinical trials, potential adverse effects and drug interactions, and challenges in standardisation. Establishing rigorous and scientifically sound quality standards, conducting larger-scale multicentre randomised controlled trials, and further elucidating the underlying mechanisms may offer effective solutions to these challenges and support the broader application of TCMs in DM management.
Keywords: diabetes mellitus